FEATURE,NILAI, KEPUASAN DAN LOYALITAS PELANGAN - Hatta, Iha Haryani (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2017)
The aim of this study was to determine the relationship of the features of the value, satisfaction, and customer loyalty; the effect on the value of customer satisfaction and loyalty; influence of satisfaction on customer loyalty. A total of 200 merchant PT. BANK XYZ as respondents was selected randomly. Analyses were performed using structural equation modeling (SEM). The analysis showed that the feature has a significant influence on customer value, but not for customer satisfaction and loyalty. The values has a significant influence on satisfaction, but not on customer loyalty. Satisfaction has a significant influence on customer loyalty. Discussion and conclusions described in the article. Keywords: features of the value, satisfaction, customer loyalty